A Design of Experiment Analysis Approach to Improve Part Quality in 3D Printing - Jabbar, Mostafa Abbas (Manufacturing Technology Journal, 2023)
Fused Deposition Modeling (FDM) is one of the widely used technologies of additive manufacturing. The concern over the surface quality and dimensional accuracy is getting increased among the research community. The design of the experimental methodology is based on the analysis of variance (ANOVA) of fractional factorial design. This analysis was used to study the effect of layer thickness, extrusion temperature, speed of deposition, and fill density on dimensional accuracy and surface roughness of the model developed by FDM. Polylactic Acid (PLA) material has been selected in this work as it is inexpensive, easy to print, and biodegradable. The results showed that layer thickness is an effective factor in determining surface roughness. Fill density (X and Z dimensions), layer thickness (Y dimension), and speed of deposition (Z dimension) are significant factors for dimensional accuracy. Regarding surface roughness, curvature was found to be significant; however, the minimum optimization point was not reached. Thus, more experiments are required to be carried out to get the minimum point. For dimensional accuracy optimization, the dimensions along X, Y, and Z were realized to be more accurate at lower levels of every factor except for fill density (D), which was optimized
Keywords: Fused Deposition Modeling; Polylactic Acid; Design Expert Software; Dimensional Accuracy; Surface Roughness